Comparative evaluation of the toxicological effect of silver salt (AgNO3) and silver nanoparticles on Cyprinus carpio synthesized by chemicals and marine algae using scanning electron microscopy. Issue 7 (25th January 2021) - Liaqat, Fareeha; Hanif, Uzma; Bahadur, Saraj; Faheem, Mehwish; Rasool, Saba; Gulzar, Sadia; Zaman, Wajid; Urooj, Zara; Shaheen, Shabnum; Munir, Mubashrah
Abstract: The widespread use of silver nanoparticles (AgNPs) results in the unintentional release into the water body. Therefore, understanding of the potentially harmful impacts of AgNPs and Ag‐salt on aquatic animals is a need of time. This study was design to analyze the oxidative stress and histopathological damages in Cyprinus carpio . The synthesis of AgNPs from Halymenia porphyraeformis and by reduction of chemical was done. Nanoparticles were characterized with UV–Visible spectroscopy, SEM, XRD, and FTIR analysis. The comparative toxicological effect of chemically synthesized silver nanoparticles (Ch‐AgNPs), green silver nanoparticles (Gr‐AgNPs), and Ag‐salt on C. carpio was analyzed. For oxidative stress analysis, different tests Lipid peroxidation (LPO), catalase, glutathione reduction (GST), and glutathione S‐transferase (GST) were performed. The highest LPO 245.168 ± 0.034 was recorded in Ch‐AgNPs‐treated gills and the lowest 56.4532 ± 0.02 was found in Gr‐AgNPs‐treated liver. Maximum GSH 56.4065 ± 0.13 was observed in Gr‐AgNPs liver and minimum 40.781 ± 0.54 was recorded in Ag‐salt gills. The maximum quantity of catalase 68.0162 ± 0.09 was noted in the Ag‐salt‐treated liver and the minimum was calculated 17.3665 ± 0.01 in the liver of Ch‐AgNPs and highest values of GST 765.829 ± 0.11 were recorded in gills of Gr‐AgNPs and lowest 633.08 ± 0.26 in the liver of Ch‐AgNPs‐treated fish. In conclusion, maximum destruction was found in the gills and liver of the fish treated with chemical and green AgNPs followed by Ag‐salt as compared to control. The adverse effects of AgNPs and Ag‐salt were probably related to the oxidative stress in the fish that lead to histopathological damage of its vital organs. Abstract : The popularization of Silver nanoparticles (AgNPs) led to the rise of their concentration in the water bodies. Some biochemical changes were observed by measuring oxidative stress on the liver and gills as a biomarker. Silver nanoparticles (AgNPs) and Ag‐salt induce histopathological effects on Cyprinus carpio . The results can assume liver and gills more sensitive to C. carpio for AgNPs as compared to Ag‐salt.